2020
DOI: 10.1149/2162-8777/ab7b44
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Contact Geometry to Reduce Forward-Bias Degradation in β-Ga2O3 Rectifiers

Abstract: We report a study of the effect of different Schottky contact orientations on maximum current achievable before failure and also temperature distributions in vertical geometry Ga2O3 rectifiers. Due to the strong anisotropy of thermal conductivity in Ga2O3, asymmetrical Schottky contacts are needed to provide higher current density with enhanced lateral thermal dissipation, symmetrical temperature profile and lower junction temperature at a specific diode current density compared to symmetrical contacts. Device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Xian et al fabricated vertical Ni/β-Ga 2 O 3 SBDs on HVPE grown (001) oriented epilayers. They studied forward bias degradation and thermal failures under high current density operation. , They found that forward-bias stress caused reverse breakdown degradation and thermally induced failure on both the SC and the epilayer due to the low thermal conductivity of Ga 2 O 3 . The simulation of temperature distributions at forward bias under different current conditions revealed that maximum temperature rise (270–350 °C) occurs at the MS contact center .…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 99%
See 4 more Smart Citations
“…Xian et al fabricated vertical Ni/β-Ga 2 O 3 SBDs on HVPE grown (001) oriented epilayers. They studied forward bias degradation and thermal failures under high current density operation. , They found that forward-bias stress caused reverse breakdown degradation and thermally induced failure on both the SC and the epilayer due to the low thermal conductivity of Ga 2 O 3 . The simulation of temperature distributions at forward bias under different current conditions revealed that maximum temperature rise (270–350 °C) occurs at the MS contact center .…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 99%
“…The maximum current density achievable with each orientation is mentioned in each diode. Reproduced with permission from ref . Licensed under a Creative Commons Attribution 4.0 International License.…”
Section: Schottky Contacts To Ga2o3mentioning
confidence: 99%
See 3 more Smart Citations